PENYULUHAN HUKUM TENTANG PERATURAN POLRI NOMOR 10 TAHUN 2022 TENTANG PENGAMANAN PENYELENGGARAAN KOMPETISI OLAHRAGA - Rahman Amin; Gatot Efrianto; Anggreany Haryani Putri; Audy Pramudya Tama; Reza Ami Putra (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
The Indonesia National Police as a state tool in the field of publicsecurity and order has the duty and authority in order to maintainpublic security and order, including the holding of footballcompetitions where today there are often riots between footballsuppoter caused by excessive fanaticism that can cause securitydisturbances and casualties. To overcome fan riots, the IndonesiaNational Police has issued Indonesia National Police RegulationNumber 10 of 2022 concerning Security for the Implementationof Sports Competitions, as a guideline for members of theIndonesia National Police in carrying out security duties to runsafely, orderly and smoothly, but in fact the provisions in thePolice Regulation are not yet known and understood by membersof the National Police serving in the sector police. The targets ofthis community service activity are members of the IndonesiaNational Police who serve in Ciracas Sector Police, East JakartaMetro Police, Metro Jaya Regional Police. The implementationof community service activities consists of the preparation stage,implementation stage, evaluation stage, and reporting the resultsof the activity output. The results of this community serviceactivity, first, that the activity runs in an orderly and smoothmanner from beginning to end in accordance with the plan thathas been made by the Implementation Team, second, this activityhas increased the knowledge and understanding of members ofthe Ciracas Sector Police, East Jakarta Metro Police, Metro JayaRegional Police regarding the substance of Indonesia NationalPolice Regulation Number 10 of 2022 concerning Security for theImplementation of Sports Competitions.